2014
DOI: 10.1682/jrrd.2013.06.0134
|View full text |Cite
|
Sign up to set email alerts
|

Pain experience of Iraq and Afghanistan Veterans with comorbid chronic pain and posttraumatic stress

Abstract: Abstract-Chronic pain and posttraumatic stress disorder (PTSD) co-occur at high rates, and Veterans from recent wars in Iraq and Afghanistan may be particularly vulnerable to both conditions. The objective of this study was to identify key aspects of chronic pain, cognitions, and psychological distress associated with comorbid PTSD among this sample of Veterans. Baseline data were analyzed from a randomized controlled trial testing a stepped-care intervention for chronic musculoskeletal pain. Operation Iraqi F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 59 publications
(77 reference statements)
2
29
1
Order By: Relevance
“…Dopamine receptor subtypes may have synergistic actions at the amygdala, whereby the aforementioned upregulation of dopamine type 1 receptors decreases inhibition while upregulation of dopamine type 2 receptors increases responsivity (Friedman, 2015), contributing to disruptions in the endogenous opioid system (Vanderkolk, 1994). Opioid dysregulation may contribute to high rates of chronic pain among patients with PTSD (Beckham et al, 1997; Outcalt et al, 2014), prompting high levels of opioid pain medication use (Outcalt et al, 2014; Phifer et al, 2011), which puts this population at risk for the development of OUDs (Chou et al, 2009; Edlund, Steffick, Hudson, Harris, & Sullivan, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Dopamine receptor subtypes may have synergistic actions at the amygdala, whereby the aforementioned upregulation of dopamine type 1 receptors decreases inhibition while upregulation of dopamine type 2 receptors increases responsivity (Friedman, 2015), contributing to disruptions in the endogenous opioid system (Vanderkolk, 1994). Opioid dysregulation may contribute to high rates of chronic pain among patients with PTSD (Beckham et al, 1997; Outcalt et al, 2014), prompting high levels of opioid pain medication use (Outcalt et al, 2014; Phifer et al, 2011), which puts this population at risk for the development of OUDs (Chou et al, 2009; Edlund, Steffick, Hudson, Harris, & Sullivan, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to potential gender differences with respect to pain experiences and reporting, prior research has consistently demonstrated a positive association between pain chronicity and emotional distress, impaired function, and health care utilization [19][20][21]. Iraq/Afghanistan-era veterans reporting pain symptoms often have comorbid mental health problems, such as posttraumatic stress disorder (PTSD) [15,22], depression [15], traumatic brain injury [22][23][24], substance use disorders [25], and increased rates of suicidal ideation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The co-occurrence of sleep disturbances and mental health symptoms with chronic pain represent an exponential increase in pain and suffering. Estimates suggest that up to 50% of individuals with chronic pain have depression, with chronic pain exacerbating depression and depression increasing pain severity and functional impairment (Banks & Kerns, 1996; Kroenke et al, 2011; Outcalt et al, 2014). Sleep difficulties are also common among patients with chronic pain, with up to 89% of patients reporting at least one sleep complaint and 53% of patients attending pain clinics presenting with clinically significant insomnia (McCracken & Iverson, 2002; Smith, Huang, & Manber, 2005; Tang, Wright, & Salkovskis, 2007).…”
mentioning
confidence: 99%